IMPROVEMENT OF THE SYSTEM OF TREASURY SERVICE IN THE SPHERE OF MANAGEMENT OF THE FUNDS OF THE STATE BUDGET OF UKRAINE (INNOVATIVE ECONOMY, 2020)
Vatamaniuk-Zelinska U.Z., Ustiuzhaninova N.V. IMPROVEMENT OF THE SYSTEM OF TREASURY SERVICE IN THE SPHERE OF MANAGEMENT OF THE FUNDS OF THE STATE BUDGET OF UKRAINEPurpose. The aim of the article is to substantiate the ways of improving the treasury system of budget execution based on the study of the practice of treasury service of the State Budget of Ukraine.Methodology of research. Formal, structural and logical methods are used in the study of the theoretical foundations of the system of treasury service in the field of funds management of the State Budget of Ukraine. Current practice of execution and analysis of budget execution – economic and statistical methods of research, generalization and comparison are also used in the article.Findings. The main aspects of the organization of the treasury system of the state budget execution of Ukraine are analyzed. The modern achievements in the development of the treasury business in Ukraine are highlighted. The dynamics of the main revenues of the State Budget for the three-year period is considered. The proposals for improving the efficiency of resource management and improving the system of treasury service of the state budget are substantiated. The main ways of improving the interaction between the Treasury bodies of Ukraine and the spending units are proposed in the process of treasury service by expenditures.Originality. The directions of the system of treasury service in the field of management of the State Budget of Ukraine are proposed by improving the system of implementation of the state budget, which would allow for the uniform distribution of revenues and expenditures in time, and also provide control over the compliance of government revenues with the adopted budget law for the current fiscal year. The range of priority tasks (minimization of time for execution of treasury transactions, optimization of ensuring the use of budget funds exclusively within the limits of the current budget legislation by strengthening control over the compliance with payment discipline by the administrators and recipients of budget funds) was substantiated due to the introduction of the software and hardware complex of the automated system “E-Kazna” in the experimental and industrial exploitation in all bodies of the Treasury of UkrainePractical value. The obtained research results will ensure observance of transparent rules of effective and rational use of state funds, prevention of budget violations both in the activities of the bodies of the State Treasury Service of Ukraine and in the work of the main spending units.Key words: State Treasury Service of Ukraine; state budget; treasury service; execution of the State Budget; revenues; expenditures.
Keywords: Key words; State Treasury Service of Ukraine; state budget; treasury service; execution of the State Budget; revenues; expenditures.